2020
DOI: 10.1101/2020.04.24.060228
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The direct and indirect effects of environmental toxicants on the health of bumble bees and their microbiomes

Abstract: Bumble bees (Bombus spp.) are important and widespread insect pollinators, but the act of foraging on flowers can expose them to harmful pesticides and environmental chemicals such as oxidizers and heavy metals. How these compounds directly influence bee survival and indirectly affect bee health via the gut microbiome is largely unknown. As the toxins and toxicants in floral nectar and pollen take many forms, we explored the genomes of core bumblebee microbes (Using RAST) for their potential to detoxify cadmiu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 106 publications
(126 reference statements)
1
11
1
Order By: Relevance
“…Lastly, we tested our beta diversity data for statistical significance in R v3.5.1 with the packages 'vegan' [54] and 'DESeq2' [55]. Data and representative code can be found on Data Dryad (doi:10.7280/D14T2K) and a preprint of this study was posted to the bioRxiv [56].…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, we tested our beta diversity data for statistical significance in R v3.5.1 with the packages 'vegan' [54] and 'DESeq2' [55]. Data and representative code can be found on Data Dryad (doi:10.7280/D14T2K) and a preprint of this study was posted to the bioRxiv [56].…”
Section: Methodsmentioning
confidence: 99%
“…of Zn between 55 and 1,158 ppm (a similar range to that measured in road verge flowers) have been found to affect caterpillar survival and development (Shephard et al, 2020). A recent study estimated that the LC50 after 7 days for bumblebees feeding on contaminated sugar water was 0.83 ppm for Cd and 66.55 ppm for Cu (Rothman et al, 2020). These are comparable to some of the highest concentrations that we measured, though a study on honeybees found that the LC50 was far greater than roadside-realistic concentrations for Cd and Pb (Di et al, 2016).…”
Section: Effects Of Pollution On Pollinator Activitymentioning
confidence: 63%
“…Further research is needed to understand if and how this might affect them, though concentrations of Pb have been negatively related to bumblebee colony growth in urban areas (Sivakoff et al., 2020), concentrations of Cd, Pb and Zn have been linked to wild bee abundance, diversity and forewing structure (Moroń et al., 2012; Szentgyörgyi et al., 2017) and concentrations of Zn between 55 and 1,158 ppm (a similar range to that measured in road verge flowers) have been found to affect caterpillar survival and development (Shephard et al., 2020). A recent study estimated that the LC50 after 7 days for bumblebees feeding on contaminated sugar water was 0.83 ppm for Cd and 66.55 ppm for Cu (Rothman et al., 2020). These are comparable to some of the highest concentrations that we measured, though a study on honeybees found that the LC50 was far greater than roadside‐realistic concentrations for Cd and Pb (Di et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Confirming earlier hypotheses [68], the significant abundance of established G. apicola variants relative to the other core members suggests that the early ileum ecosystem and/or S. alvi specifically selects for G. apicola diversity of function (Table 1). Correspondingly, G. apicola strains show notable variation across many functional categories including oxidative stress and carbohydrate utilization, while S. alvi strains are typically fixed for similar functions indicating competition and host fidelity respectively [38,48,[71][72][73].…”
Section: Transmission and Assemblymentioning
confidence: 99%